Transcriptomics combined with physiological analysis reveals the mechanism of cadmium uptake and tolerance in Ligusticum chuanxiong Hort. under cadmium treatment - Zhang, Zhanling; Zhong, Lele; Xiao, Wanting; Du, Yaping; Han, Guiqi; Yan, Zhuyun; He, Dongmei; Zheng, Chuan (Frontiers in Plant Science, 2023)
Ligusticum chuanxiong Hort. is a widely used medicinal plant, but its growth and quality can be negatively affected by contamination with the heavy metal cadmium (Cd). Despite the importance of understanding how L. chuanxiong responds to Cd stress, little is currently known about the underlying mechanisms. To address this gap, we conducted physiological and transcriptomic analyses on L. chuanxiong plants treated with different concentrations of Cd 2+ (0, 5, 10, 20, and 40 mg•L -1 ). Our findings revealed that Cd stress led to inhibited biomass accumulation and root development, while activating the antioxidant system in L. chuanxiong. Root tissues were the primary accumulation site for Cd in this plant species, with Cd being predominantly distributed in the soluble fraction and cell wall. Transcriptomic analysis demonstrated down-regulation of differential genes involved in photosynthetic pathways under Cd stress. Conversely, the plant hormone signaling pathway and the antioxidant system exhibited positive responses to Cd regulation. Additionally, the expression of differential genes related to cell wall modification was up-regulated, indicating potential enhancements in the root cell wall's ability to sequester Cd. Several differential genes associated with metal transport proteins were also affected by Cd stress, with ATPaes, MSR2, and HAM3 playing significant roles in Cd passage from the apoplast to the cell membrane. Furthermore, ABC transport proteins were found to be key players in intravesicular compartmentalization and efflux of Cd. In conclusion, our study provides preliminary insights into the mechanisms underlying This is a provisional file, not the final typeset article Cd accumulation and tolerance in L. chuanxiong, leveraging both physiological and transcriptomic approaches. The decrease in photosynthetic capacity and the regulation of plant hormone levels appear to be major factors contributing to growth inhibition in response to Cd stress. Moreover, the up-regulation of differential genes involved in cell wall modification suggests a potential mechanism for enhancing root cell wall capabilities in isolating and sequestering Cd. The involvement of specific metal transport proteins further highlights their importance in Cd movement within the plant.